Numerical investigation of flow unsteadiness and heat transfer on suction surface of rotating airfoils within a gas turbine cascade - Guo, Liang; Yan, Yuying; Sun, Wanchen; Zhu, Jie (Elsevier, 2017)
The effects of the periodical turbulence and pressure fluctuation on suction surface heat transfer over airfoils of a row of rotor blades with a certain type have been investigated numerically in this paper. The calculation is performed using model with the numerical results of pressure fluctuation and heat transfer performance over 4 sample points being analyzed and compared with existing experimental data. It shows that the static pressure change has significant impact on heat transfer performance of the fore suction surface, especially in the active region of the shock waves formed from the trailing edge of upstream nuzzles. While, for the rear suction surface, the flow turbulence contributes more to the heat transfer change over the surface, due to the reduced pressure oscillation through this region. Phase shifted phenomenon across the surface can be observed for both pressure and heat transfer parameters, which should be a result of turbulence migration and wake passing across the airfoil.